THE INFLUENCE OF CELEBRITY ENDORSERS, BRAND IMAGE, AND PRICE PERCEPTION ON PURCHASE INTENTION FOR ERIGO BRAND PRODUCTS - Gusti Ngurah Andhika D. Madhawa; Komang Agus Satria Pramudana (Adisam Publisher, 2025)
The fashion sector is expanding at a rapid pace amidst intense market competition, prompting companies to formulate efficient marketing strategies. Erigo stands out as one of the leading local fashion brands in Indonesia. This research investigates how celebrity endorsement, brand image, and perceived pricing affect consumer intentions to purchase Erigo-branded products. The research focuses on individuals living in Denpasar City who are potential buyers of Erigo apparel. Employing a non-probability sampling method, the study involves 100 respondents. The collected data is analyzed using multiple linear regression. Findings reveal that celebrity endorsers, brand image, and price perception significantly and positively impact consumers’ intention to purchase Erigo products